An Update on Pulmonary Hypertension in Coronavirus Disease-19 (COVID-19): Pulmonary Hypertension and COVID -19 - Mishra, Ajay; Lal, Amos; Sahu, Kamal Kant; George, Anu Anna; Martin, Kevin; Sargent, Jennifer (Acta Biomedica Atenei Parmensis, 2020)
Coronavirus 19 disease (COVID-19) continues to be a pandemic with global implications.  Respiratory system involvement is the most common manifestation in symptomatic patients.  In this literature review, we describe the diagnosis, management, and implications of pulmonary hypertension (PH) among patients with COVID-19.  We defined pulmonary hypertension as increasing mean pulmonary artery pressure (mPAP) of ≥ 25 mm Hg at rest.  In our literature search, we identified 4 articles with details on pulmonary hypertension.  Among these, two reported various echocardiographic details for diagnosing pulmonary hypertension.  In 1 study evidence of pulmonary hypertension was noted in 13.4% of patients.  Patients with severe COVID-19 were reported to have a higher proportion of pulmonary hypertension as compared to mild COVID-19 disease [22% vs 2%].  Elevated pulmonary artery systolic pressure was significant in predicting mortality.  COVID-19 patients with chronic obstructive pulmonary disease, congestive heart failure, myocardial injury, pulmonary embolism, and prior pulmonary hypertension were at a higher risk of worsening pulmonary hypertension.  Multiple mechanisms for developing pulmonary hypertension that have been postulated are i) concomitant worsening myocardial injury, ii) cytokine storm, endothelial injury, hypercoagulability attributing to development of venous thromboembolism, iii) and the presence of thrombotic microangiopathy.  Among patients with severe COVID-19 disease and pulmonary hypertension, complications including acute respiratory distress syndrome, acute myocardial injury, the requirement of intensive care unit admission, the requirement of mechanical ventilation, and mortality are higher.